Experimental study of Bias Acoustic Liner on nacelle lip-skin/ Qummare Azam ...[et al.] - Azam1,, Qummare; Ismail1*, Mohd Azmi; Mazlan2, Nurul Musfirah (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
The paper demonstrates the effect of Bias Acoustic Liner for nacelle lip-skin for civil aircraft. The effect of drag on nacelle lip-skin porous surface profile with liner. Additionally, the absorption of noise that reduced by using of Bias acoustic liner has been discussed. An acoustically absorbent material is employed with honeycomb liner for the required acoustic attenuation features for the aircraft engines. The BAL system behaves differently at different positions, around the rotor fan to absorb the fan noise; however, at the nacelle position along with anti-icing system, it shows dual nature i.e., noise reduction as well as drag reduction by using of bias flow through the micro-channels of the liner. The experiment runs between 00-50 (degree) angle of attack and Reynolds no. 2.2×105 to 5.8×105 to achieve drag reduction by 22%. At 20 angles of attack found the effective inclination for drag reduction. Backplate using at the large area over where the acoustic reducing material is used from the close source. In this paper, we will also discuss briefly Bias Acoustic Liner applications in aircraft engines.